Dependence of Permeability of SPEV Cell Membranes for Molecules of Ethylene Glycol and 1,2-Butane Diol on Temperature - Chernobay, N. A.; Kovalenko, I. F.; Koschiy, S. V.; Rozanov, L. F. (Problems of Cryobiology and Cryomedicine, 2009)
Using the method of volumometry the permeability coefficients for SPEV cell membranes of ethylene glycol (EG) and 1,2-butane diol (1,2-BD) at temperatures of 35, 18 and 7°C have been determined. The calculated within the range of temperatures of 35–7°C values of permeability activation energy for molecules of EG and 1,2-BD make 45.07 and 55.35 kJ/mol, correspondingly. The differences in membrane permeability for EG and 1,2-BD molecules are the most manifested at 35°C and are absent at 7°C.